Inhibitor of Apoptosis Proteins Determines Glioblastoma Stem‐Like Cell Fate in an Oxygen‐Dependent Manner. (28th March 2019) - Soubéran, Aurélie; Cappaï, Jessica; Chocry, Mathieu; Nuccio, Christopher; Raujol, Julie; Colin, Carole; Lafitte, Daniel; Kovacic, Hervé; Quillien, Véronique; Baeza‐Kallee, Nathalie; Rougon, Geneviève; Figarella‐Branger, Dominique; et al.
Abstract: In glioblastomas, apoptosis inhibitor proteins (IAPs) are involved in apoptotic and nonapoptotic processes. We previously showed that IAP inhibition induced a loss of stemness and glioblastoma stem cells differentiation by activating nuclear factor‐κB under normoxic conditions. Hypoxia has been shown to modulate drug efficacy. Here, we investigated how IAPs participate in glioblastoma stem‐like cell maintenance and fate under hypoxia. We showed that in a hypoxic environment, IAPs inhibition by GDC‐0152, a small‐molecule IAPs inhibitor, triggered stem‐like cell apoptosis and decreased proliferation in four human glioblastoma cell lines. We set up a three‐dimensional glioblastoma spheroid model in which time‐of‐flight secondary ion mass spectrometry analyses revealed a decrease in oxygen levels between the periphery and core. We observed low proliferative and apoptotic cells located close to the hypoxic core of the spheres and glial fibrillary acidic protein + cells at their periphery. These oxygen‐dependent GDC‐0152 antitumoral effects have been confirmed on human glioblastoma explants. Notably, serine–threonine kinase activation analysis revealed that under hypoxic conditions, IAP inhibition activated ataxia telangiectasia and Rad3‐related protein signaling. Our findings provide new insights into the dual mechanism of action of IAP inhibitors that depends on oxygen level and are relevant to their therapeutic application in tumors.Stem Cells 2019;37:731–742 Abstract : Summary of apoptosis inhibitor proteins inhibition effect depending on oxygen level in glioblastoma.